Benchmarking higher education programs through alignment analysis based on the revised Bloom's taxonomy. Issue 8 (29th November 2018) - Lau, Kwok Hung; Lam, Tri Khai; Kam, Booi Hon; Nkhoma, Mathews; Richardson, Joan
Abstract : Purpose: The purpose of this paper is to propose a scalable quantitative approach to evaluate alignment within and between courses and programs in higher education for benchmarking purpose. Design/methodology/approach: The revised Bloom's taxonomy, which combines a cognitive process dimension and a knowledge dimension, is used as a basis for categorizing national standards, program and course learning outcomes (CLOs) and assessment methods. Alignments between programs and national standards, programs and courses and assessment tasks and courses are then measured using a series of Cohen's κ statistics. Two undergraduate business programs offered at an Australian university were used as examples to demonstrate the proposed method as an alignment evaluation tool. Findings: The findings reveal that the two sample programs are better aligned with national standards than with their respective constituent courses. The degree of alignment between CLOs and assessment methods varies from course to course within the programs. This might be related to the lack of clarity of some learning outcome statements and the complexity of certain assessment methods. Research limitations/implications: This study lends insight into the use of an alignment mapping for benchmarking academic programs in higher education. To serve mainly as an illustration of the proposed approach, the case study is limited to two undergraduate business programs offered at the same university. Practical implications: Universities can use the proposed approach to benchmark their academic programs against the national standards and similar programs offered by other competing educational institutions. The alignment indices can also serve as yardsticks to continuously improve the consistencies within and among academic programs to ensure quality. Originality/value: The proposed method offers a consistent basis to compare the degrees of alignment of different higher education programs with national standards and their respective constituent courses, hence enabling benchmarking for continuous improvement. It also reveals how the alignment between different parameters in teaching and learning can be improved, thereby facilitating incremental learning and enhancing student performance.